Activity report: CSV Monitoring and Evaluation Plan - Eitzinger, Anton; Bonilla Findji, Osana; Andrieu, Nadine; Feil, Christian; Bejarano, Gustavo (2019)
This progress report focuses on the development of GeoFarmer (V1). It describes how we adapted the GeoCitizen application framework and developed new user interfaces as GeoFarmer, for the purpose of using it in the agricultural development projects, and more specific, for the monitoring and evaluation of CSA adoption in CCAFS Climate-Smart villages.